Desenvolvimento de um portal educativo sobre fertilização in vitro com oócitos doados - Robin, Fernanda Kunrath (Universidade do Vale do Rio dos Sinos, 2021)
The assisted human reproduction technology (ART) has been increasingly sought after by couples / people with some type of infertility. The postponement of maternity, genetic and oncological diseases and early ovarian failure are the main reasons to increase in the number of in-vitro fertilization cycles with oocyte donation. The main objective of this study was to develop and validate an educational portal providing information and guidance about IVF cycle with donor eggs. Methodological study was developed in three phases: 1) a quantitative descriptive study that aimed to: a) characterize the women who underwent IVF cycles with donor eggs at the assisted reproduction clinic in study, from January / 2017 to April / 2020. The variables were: age, origin and diagnosis that allows them to resort to this technique; b) characterize the IVF cycles with donor eggs as to the number carried out each year of this research, origin of the egg, Preimplantation genetic diagnosis (PGD) technique usage, number of embryos transferred per cycle and cycle results and outcomes; 2) qualitative study, which investigated how heterosexual couples and women faced the IVF cycle with donor eggs; 3) construction and validation of the educational portal. In Step 1, quantitative data collection was performed in the records of the 222 women who underwent IVF cycles with donor eggs during the study period. Descriptive statistics were used for data analysis. In Step 2, referring to the qualitative study, the participants were heterosexual couples and women who became pregnant at the clinic in study, from January 2017 to February 2020 through eggs donation. The data collection was carried out by an electronic questionnaire, with open questions about the topic under study. The data processing was performed using the software IRAMUTEQ. In Step 3, the educational portal was made considering the results of qualitative and quantitative studies. The steps followed: a) needs analysis; b) design; c) development; d) implementation and evaluation; e) overhaul and maintenance. The themes elaboration of the portal emerged from the speeches of the participants of the qualitative stage. The content was prepared based on current theoretical framework, standards and current Brazilian legislation. The validation of the portal content was performed by 10 health women judges: nurses (6), midwives (2), matron (1) and surgical instrumentalist (1); from Brazil (06), Peru (02), Argentina (01) and Chile (01). The analysis of portal validation was by the Content Validity Index (CVI) & gt; 0.8, obtaining CVI average of 0.96. The validation of the portal technology occurred through the program Google Lighthouse, obtaining 91.5 points, which demonstrated that the portal has great performance criteria. The results show a high level of agreement for the applicability of the educational portal, which may support the dissemination of the egg donation treatment. In addition, the portal can be used as a basis for research by couples, women / men who needs to resort to egg donation, health professionals and people interested in the topic. , the product generated in this research consists of the Educational Portal: Understanding Egg donation, accessed through the domain https://nilofrantz.com.br/portalovodoacao. It is the first Educational Portal related to egg donation in Brazil, with real impact, considering the knowledge dissemination of on the topic, contributes to promote the involved people protagonistin the process of in vitro fertilization with a donor egg.
Keywords: Fertilização in vitro; Enfermeira; Doação de oócitos; Técnicas de reprodução assistida; In vitro fertilization; Nurse; Oocyte donation; Assisted reproduction techniques; ACCNPQ::Ciências da Saúde::Enfermagem